A STRUCTURAL ANALYSIS OF AUDRE LORDE’S RACISM POETRY: IT’S INTRINSIC AND EXTRINSIC ELEMENT - Ghina Nuryana Hasanah; Marwito Wihadi; Nida Amalia Asikin (Journey: Journal of English Language and Pedagogy, 2023)
This research aims to analyze and identify intrinsic elements in the form of theme, figurative language, and diction, then analyze extrinsic elements in the form of social elements in poetry making and analyze racism reflected in Audre Lorde's poems entitled Power (1978), Who Said It Was Simple (1973) and A Woman Speaks (1984). The method use in this research was a qualitative method. Reading the poem in order to comprehend its overall meaning and discover the meaning which was primarily the essence related to the topic was how the data was collected. This research, there were found 16 data from three themes, 42 figurative languages, 38 dictions, and 17 racism data from three Audre Lorde poems. In addition, There were various manifestations of racism in the poem "Power," including skin color, injustice, segregation, and racial prejudice. The poem "Who Said It Was Simple" has elements of racism related to homophobia, gender, and skin color. The poem "A woman speaks" contains multiple instances of racism, including prejudice based on race, gender, and skin tone. This research is recommended for someone who is interested in literary works, especially poetry, but further research can analyze more broadly in other literary works such as novels, short stories and, songs